The life and legacy of Professor John Senders - Hancock, P.; Hancock, Gabriella; Sellen, Abigail (Human Factors, 2019)
This session looks to serve the purpose of recalling and recounting the life and contributions of Professor John Senders. The contributors to this session include his direct colleagues, his students, his co-authors, those whom he inspired, and even members of his family. These designations are not exclusive! Senders made so many contributions across virtually a century of his lifetime that we are constrained to provide only selective highlights in this memorial session, such as John being named the winner of an “Ig-Nobel” Award. We shall each survey particular works which influenced us, but interweave those observations with personal experiences that can serve to reveal John the character, who was so much more than the simple written record that he has left behind.